Anti‐CD3 treatment up‐regulates programmed cell death protein‐1 expression on activated effector T cells and severely impairs their inflammatory capacity. Issue 2 (16th March 2017) - Wallberg, Maja; Recino, Asha; Phillips, Jenny; Howie, Duncan; Vienne, Margaux; Paluch, Christopher; Azuma, Miyuki; Wong, F. Susan; Waldmann, Herman; Cooke, Anne
Abstract : We have used transfer of GFP‐labelled islet specific Th1‐differentiated effector cells to investigate the effects of anti‐CD3 treatment specifically on the pathogenic effector cell compartment. We find that anti‐CD3 treatment does not specifically kill islet‐specific effector cells, but rather reduces metabolic activity, increases PD‐1 expression, and abolishes the inflammatory capacity of these cells Summary: T cells play a key role in the pathogenesis of type 1 diabetes, and targeting the CD3 component of the T‐cell receptor complex provides one therapeutic approach. Anti‐CD3 treatment can reverse overt disease in spontaneously diabetic non‐obese diabetic mice, an effect proposed to, at least in part, be caused by a selective depletion of pathogenic cells. We have used a transfer model to further investigate the effects of anti‐CD3 treatment on green fluorescent protein (GFP) + islet‐specific effector T cells in vivo . The GFP expression allowed us to isolate the known effectors at different time‐points during treatment to assess cell presence in various organs as well as gene expression and cytokine production. We find, in this model, that anti‐CD3 treatment does not preferentially deplete the transferred effector cells, but instead inhibits their metabolic function and their production of interferon‐ γ . Programmed cell death protein 1 (PD‐1) expression was up‐regulated on the effector cells from anti‐CD3‐treated mice, and diabetes induced through anti‐PD‐L1 antibody could only be reversed with anti‐CD3 antibody if the anti‐CD3 treatment lasted beyond the point when the anti‐PD‐L1 antibody was washed out of the system. This suggests that PD‐1/PD‐L1 interaction plays an important role in the anti‐CD3 antibody mediated protection. Our data demonstrate an additional mechanism by which anti‐CD3 therapy can reverse diabetogenesis.